2010
DOI: 10.1038/jp.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of HIV vertical transmission in a cohort of women under a PMTCT program at three peri-urban clinics in a resource-poor setting

Abstract: Objective:To identify the risk factors of HIV vertical transmission in pregnant women.Study Design:Observational cohort study. Between 2002 and 2003, 479 HIV-infected pregnant women in a PMTCT (prevention of the mother-to-child transmission) program were followed up with their infants at delivery, until 15 months with infant HIV testing.Results:Of these 281 infants had a definitive HIV result by 15 months of age, and 31.7% of the infants become HIV infected. In univariate analysis the risk factor identified we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
(17 reference statements)
4
23
0
Order By: Relevance
“…However, studies have been done which have found HIV in cells found in electively aborted foetuses in the first trimester of pregnancy (Lewis, et al, 1990). Factors that are associated with transmission during pregnancy are: maternal genital infections, as well as malaria, which can damage the placenta and allow passage of HIV cells (Gumbo et al, 2010;ter Kuile, et al, 2004;Bloland, et al, 1995;Inion, et al, 2003);and, gender, where female infants are thought to be at double the risk of infection than males (Biggar, et al, 2006).…”
Section: Mother-to-child Transmission Of Hiv (Mtct)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have been done which have found HIV in cells found in electively aborted foetuses in the first trimester of pregnancy (Lewis, et al, 1990). Factors that are associated with transmission during pregnancy are: maternal genital infections, as well as malaria, which can damage the placenta and allow passage of HIV cells (Gumbo et al, 2010;ter Kuile, et al, 2004;Bloland, et al, 1995;Inion, et al, 2003);and, gender, where female infants are thought to be at double the risk of infection than males (Biggar, et al, 2006).…”
Section: Mother-to-child Transmission Of Hiv (Mtct)mentioning
confidence: 99%
“…Factors associated with transmission are: early mixed-feeding i.e. before six months of age when the infant's gastrointestinal tract is still immature and susceptible to damage (Coovardia, et al, 2007), abrupt breastfeeding cessation (WHO, 2010b), and mastitis or breast abscess (Gumbo, et al, 2010).…”
Section: Mother-to-child Transmission Of Hiv (Mtct)mentioning
confidence: 99%
“…HIV-1-positive mother and infant pairs were offered 200 mg of single dose nevirapine during labor and 2 mg/kg body weight within 72 h postdelivery, respectively. 18 Mothers were encouraged to exclusively breastfeed during the first 6 months. Infants' venous EDTA whole blood and plasma samples were collected at delivery, at 6 weeks, and at 4 and 9 months postpartum, and thereafter every 3 months until 2 years, thus generally coinciding with infant immunization visits.…”
Section: Study Population and Proceduresmentioning
confidence: 99%
“…EDTA-anticoagulated venous blood samples were processed within 6 h for full blood counts using the Abbott Diagnostic Cell Dyne 3500R SL Hematology Analyser. Mothers were screened for sexually transmitted infections as previously described by Gumbo et al 18 …”
Section: Mothers' Testsmentioning
confidence: 99%
“…30,34,35 Furthermore, maternal T vaginalis infection in an HIV-infected woman nearly doubles the risk of vertical transmission of HIV to the infant. 36 Interestingly, HIV-infected women are less likely to shed HIV vaginally after receiving treatment for trichomoniasis. 37,38 However, there are no data to show that treating T vaginalis can reverse the increased risks of HIV acquisition or transmission.…”
Section: Adverse Outcomesmentioning
confidence: 99%